A Case of Primary Ileocecal Lymphoma - Wulyo Rajabto; Djumhana Atmakusuma; Ivan Onggo S; Dadang Makmun (The Indonesian Society for Digestive Endoscopy, 2016)
Primary lymphoma in gastrointestinal tract is not very common. Ileocecal region is the commonest site for primary lymphoma and diffuse large B cell lymphoma (DLBCL) is the most prevalent subtype. The clinical presentation in this condition is pain in right lower quadrant region and this can very confusing since many diseases can also cause this problem like infection and inflammatory disease. In this paper, we report a case of primary lymphoma subtype DLBCL in ileocecal region that come to emergency department with ileus obstruction. Abdominal computerized tomography (CT) scan and colonoscopy revealed tumour in ileocecal region ascendens colon. Hemicolectomy was performed and the specimen was sent to pathology which revealed non-Hodgkin lymphoma with subtype DLBCL CD20 (+). The patient had undergone of Rituximab, Cyclophosphamide, Doxorubicine, Vincristin, and Prednison (RCHOP) chemotherapy regimen and had complete remission.